Optimal cutoff points for the detection of undiagnosed type 2 diabetes, hypertension and metabolic syndrome in Mexican adults Puntos de corte óptimos para la detección de diabetes tipo 2, hipertensión y síndrome metabólico no diagnosticados en adultos mexicanos - Rosalba Rojas-Martínez; Carlos A Aguilar-Salinas; Aída Jiménez-Corona (Instituto Nacional de Salud Pública, 2012)
OBJECTIVE: To compare the waist circumference cutoff points established by the American Heart Association and the National Heart, Lung and Blood Institute (AHA/NHLBI) with those of the International Diabetes Federation (IDF) for the screening of diabetes, hypertension, and metabolic syndrome in Mexican adults. MATERIAL AND METHODS: This study comprised a subsample of the ENSANUT 2006. Subjects without diabetes and hypertension and non-pregnant women were included. Sensitivity, specificity, and predictive values were compared using AUC and the positive likelihood ratio test [LR(+)]. RESULTS: In subjects aged ≥40 years, sensitivity for detection of diabetes and hypertension was higher for the IDF thresholds (85.34 and 86.87%, respectively) compared with those of the AHA/NHLBI (59.49 and 52.41%, respectively). LR(+) were higher for IDF thresholds compared with AHA/NHLBI. Similar results in subjects aged ≥65 years were observed. CONCLUSIONS: The measurement of abdominal obesity defined by the IDF was a better screening tool for diabetes and hypertension, considering that initially a high sensitivity and low cost tool at population level is required. OBJETIVO: Comparar los puntos de corte de circunferencia de cintura de la American Heart Association and the National Heart, Lung and Blood Institute (AHA/NHLBI) y la International Diabetes Federation (IDF) para escrutinio de diabetes, hipertensión arterial y síndrome metabólico en adultos mexicanos. MATERIAL Y MÉTODOS: Se analizó una submuestra de la ENSANUT 2006 incluyendo sujetos sin diabetes o hipertensión y mujeres no embarazadas. Se comparó la sensibilidad, especificidad y valores predictivos mediante AUC y la razón de verosimilitudes positiva [LR(+)]. RESULTADOS: En personas ≥40 años, la sensibilidad para detección de diabetes e hipertensión usando el criterio de la IDF fue de 85.34% (LR(+)=1.1) y 86.87% (LR(+)=1.1); mientras que para el criterio de la AHA/NHLBI fue de 59.49% (LR(+)=1.34) y 52.41% (LR(+)=1.21). Los resultados fueron similares en personas ≥65 años. CONCLUSIONES: La obesidad abdominal según la IDF fue superior como procedimiento de tamizaje de diabetes e hipertensión, considerando que se requiere de una prueba inicial más sensible y de bajo costo para ser aplicada a nivel poblacional.